2018
DOI: 10.1016/j.cmi.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the BacT/Alert Virtuo Microbial Detection System for the culture of sterile body fluids: prospective multicentre study

Abstract: The BacT/Alert Virtuo system was equivalent to the 3D system in organism recovery from sterile body fluid culture but showed faster detection of growth as a result of design enhancements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In this study, the bile samples were incubated and separated by a BacT/Alert3D automated blood culture instrument [ 12 ] in accordance with international standard operation procedures for bacterial detection [ 13 , 14 ]; this method can guarantee the growth and accurate identification of specific organisms, even if the samples contained multiple species [ 13 ]. According to the data obtained from bile specimens from 560 AP patients in hospitals, 120 positive cases and 132 strains of pathogenic bacteria were identified, with a positive infection rate of 21.43%, which was lower than that obtained in an analysis without stratification by sample type [ 15 ], similar to those in blood culture specimens in some hospitals in northern China without disease classification [ 16 ], and higher than those in blood culture specimens in some hospitals in central cities of China [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the bile samples were incubated and separated by a BacT/Alert3D automated blood culture instrument [ 12 ] in accordance with international standard operation procedures for bacterial detection [ 13 , 14 ]; this method can guarantee the growth and accurate identification of specific organisms, even if the samples contained multiple species [ 13 ]. According to the data obtained from bile specimens from 560 AP patients in hospitals, 120 positive cases and 132 strains of pathogenic bacteria were identified, with a positive infection rate of 21.43%, which was lower than that obtained in an analysis without stratification by sample type [ 15 ], similar to those in blood culture specimens in some hospitals in northern China without disease classification [ 16 ], and higher than those in blood culture specimens in some hospitals in central cities of China [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fastidious and slowly growing microorganisms or broad-spectrum antimicrobial treatment before obtaining pleural/peritoneal fluids for culture often leads to false-negative results. Moreover, bacterial culture usually takes 1 to 5 or more days (She et al 2018 ). For highly suspected patients with infections, the shorter the diagnostic procedure, the better the clinical outcome may be.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that different blood culture systems gave close results to each other. Duration time of culture positivity was shorter and isolation rate was higher than the standard culture (16).…”
Section: Discussionmentioning
confidence: 85%